2003
DOI: 10.1124/jpet.102.048454
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relations of Successful Pharmacologic Chaperones for Rescue of Naturally Occurring and Manufactured Mutants of the Gonadotropin-Releasing Hormone Receptor

Abstract: We expressed a test system of wild-type (WT) rat (r) and human (h) gonadotropin-releasing hormone (GnRH) receptors (GnRHRs), including naturally occurring (13) and manufactured (five) "loss-of-function" mutants of the GnRHR. These were used to assess the ability of different GnRH peptidomimetics to rescue defective GnRHR mutants and determine their effect on the level of membrane expression of the WT receptors. Among the manufactured mutants were the shortest rGnRHR C-terminal truncation mutant that resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(138 citation statements)
references
References 32 publications
2
136
0
Order By: Relevance
“…Cells were treated with pharmacoperones as previously reported (Janovick et al, 2001;Janovick et al, 2003), where indicated. Cells were washed then "pre-loaded" for 6 hours (unless otherwise indicated) with 4 μCi/ml myo-[2-3 H(N)]-inositol in 0.25 ml DMEM (prepared without inositol; Brothers et al, 2004).…”
Section: Inositol Phosphate (Ip) Assaysmentioning
confidence: 99%
“…Cells were treated with pharmacoperones as previously reported (Janovick et al, 2001;Janovick et al, 2003), where indicated. Cells were washed then "pre-loaded" for 6 hours (unless otherwise indicated) with 4 μCi/ml myo-[2-3 H(N)]-inositol in 0.25 ml DMEM (prepared without inositol; Brothers et al, 2004).…”
Section: Inositol Phosphate (Ip) Assaysmentioning
confidence: 99%
“…It is also worth remarking on the observation that chemical structures, which bind to the active site (or at least compete with the ability of agonists to do so), also serve as pharmacoperones, causing misfolded proteins to fold in a way that makes them fold correctly and escape the QCS (Morello et al, 2000;Janovick et al, 2003a;Noorwez et al, 2004;Hawtin, 2006). This observation suggests that there may be a relation between proper construction of the active site and proper overall construction of the receptor.…”
Section: Relation Between the Overall Receptor Structure And The Smentioning
confidence: 99%
“…For that reason they may come from diverse chemical classes. In the case of the GnRHR, pharmacoperones coming from classes as diverse as erythromycin macrolides, indoles, and quinolones have been identified (Janovick et al, 2003a).…”
Section: Of-function Diseases or Abnormalities Caused By Particular Gmentioning
confidence: 99%
See 2 more Smart Citations